Evaluation of an ELISA-based visualization microarray chip technique for the detection of veterinary antibiotics in milk. (December 2019) - Du, Bingyao; Wen, Fang; Guo, Xiaodong; Zheng, Nan; Zhang, Yangdong; Li, Songli; Zhao, Shengguo; Liu, Huimin; Meng, Lu; Xu, Qingbiao; Li, Ming; Li, Fadi; et al.
Abstract: Antibiotics are increasingly found in dairy products. To ensure consumer safety, rapid screening methods which are accurate and cost-effective are highly in demand. A multiplexed detection technology was tested for quantification of these four kinds of antibiotics simultaneously in milk. The visual microarray technology based on enzyme-linked immunosorbent assays was utilized in this method, which can detect multiple target molecules simultaneously. This colorimetric technology provides direct results that can be detected using common commercial microplate scanners. The limit of detection (LOD) were calculated as 3.30, 3.39, 2.42 and 4.88 μg kg −1 for quinolones, tetracycline, lincomycin and streptomycin, respectively. The limits of quantity (LOQ) were defined as 8.97, 8.43, 5.36 and 10.97 μg kg −1 for quinolones, tetracycline, lincomycin and streptomycin, respectively. The accuracy of method was also adequate for these four substances with the recovery rates ranging from 77.6% to 116.4% were obtained for the detection of practical samples. According to our evaluation, this methodology can be used for rapid screening of antibiotics in internal quality control programs in dairy industry. Highlights: The multiplexed detection method for testing veterinary antibiotics in milk were evaluation. The ELISA-based visualization microarray chip technique using 96-well microplate. The limit of detection are less than the MRL established in China, the CAC and the EU. The accuracy of method was adequate for these four veterinary antibiotics.